Corrosion, processes and advanced materials in industry : selected peer reviewed papers from the 3rd (Israel) international conference, corrosion, advanced materials and processes in industry May 29th-31th 2007, Beer-Sheva, Israel - Eliezer, Amir (Advanced materials research ;, 2010)
The aim of this edition is to increase the worldwide awareness of corrosion-related issues and to develop national and international industrial-scientific cooperation in order to find practical solutions to the US